Assessment of the Impact of a Structured Educational Program on PCOS Knowledge Among Adolescent Girls in a Chosen Area of Tarn Taran District, Punjab - Bikramjit Kaur; Gagandeep Kaur; Rachna Gill (International Journal of Women's Health Nursing And Practices, 2023)
Polycystic ovary syndrome (PCOS) is a health condition characterized by elevated levels of androgen hormones, irregular menstrual patterns, and the existence of small cysts on one or both ovaries. The disorder can be morphological or biochemical. Prevention of PCOS includes lifestyle modifications that are to manage weight, exercise, and dietary changes. Aim and Objectives: The main goal of this study was to assess the efficacy of a structured educational program in improving the understanding of PCOS among adolescent girls. Methodology: This study utilized quantitative research methodology and employed a pre-experimental design. The sample comprised 60 adolescent girls selected from specific regions within Tarn Taran district. Convenience sampling was the technique of choice, and a self-structured questionnaire was employed to evaluate their knowledge. A structured teaching program was delivered and post-test was taken. Reliability and validity of the tool was established. Results: The findings show that majority of adolescent girls belongs to age group of 20 years. Majority of adolescent girls had normal body mass index. The onset of menarche occurs after the age of 12 years. Maximum adolescent girls were vegetarian and belonged to rural areas. A significant number of adolescent girls consumed a high amount of junk food. Majority of adolescent girls had normal menstrual cycle and have occasional exercise routine. Regarding knowledge, majority of girls had average knowledge (96.7%) regarding PCOS during pretest. The findings show that after post-test all (100%) the girls had good knowledge regarding PCOS. Conclusion: Majority of adolescent girls had good knowledge regarding PCOS.
Keywords: Adolescents; Knowledge; Polycystic ovary syndrome (PCOS); structured teaching program